Analisis Ekonomi Islam Terhadap Peran Strategis PT Eastern Logistics Shorbase Lamongan dalam Rantai Pasok Nasional - Ahmad Badrut Tamam; Moh Afthon Ilman Huda; Ummul Karomah (Al-Musthofa: Journal of Sharia Economics, 2025)
Indonesia, an archipelago, faces complex logistics challenges, resulting in high domestic logistics costs (14-30% of GDP) and a declining Logistics Performance Index (LPI). This study aims to deeply describe the strategic role of PT Eastern Logistics Shorebase (ELS) Lamongan in the national supply chain. Using a qualitative descriptive approach with data collected through in-depth interviews, direct observation, and documentation, and analyzed using the Miles and Huberman model (data reduction, data display, conclusion drawing), the research highlights ELS's significant contributions. The findings reveal that ELS, a world-class shuttle-classer facility in Lamongan, East Java, acts as a crucial offshore-onshore logistics hub. It significantly reduces distribution costs and time (saving over IDR 100 billion in five years for oil and gas operations), integrates multimodal logistics through IT-based systems, and fosters strategic collaborations with national stakeholders like SKK Migas and Pertamina. Furthermore, an Islamic economic analysis demonstrates that ELS's operations align with Sharia principles, emphasizing efficiency (iqtishad), equitable distribution (adl), collaboration (ta’awun), innovation (itqan), and public welfare (maslahah). ELS serves as a model for regional logistics development, enhancing inter-island connectivity, relieving pressure on major ports, and accelerating the equitable distribution of national logistics infrastructure, proving that efficient and profitable economic activities can align with Sharia principles for the greater good.